Monitoring water stress in Mediterranean semi-natural vegetation with satellite and meteorological data - Moreno, a.; Maselli, F; Chiesi, M; Genesio, L; Vaccari, F; Seufert, G; Gilabert, M.a. A (International Journal of Applied Earth Observation and Geoinformation, 2014)
In arid and semi-arid environments, the characterization of the inter-annual variations of the light use efficiency ε due to water stress still relies mostly on meteorological data. Thus the GPP estimation based on procedures exclusively driven by remote sensing data has not found yet a widespread use. In this work, the potential to characterize the water stress in semi-natural vegetation of three spectral indices (NDWI, SIWSI and NDI7) – from MODIS broad spectral bands – has been analyzed in comparison to a meteorological factor (Cws). The study comprises 70 sites (belonging to 7 different ecosystems) uniformly distributed over Tuscany, and three eddy covariance tower sites. An operational methodology, which combines meteorological and MODIS data, to characterize the inter-annual variations of ε due to summer water stress is proposed. Its main advantage is that it relies on existing series of meteorological data characterizing each site and allows calculating a typical Cws profile that can be “updated” (C∗ ws) for the actual conditions using MODIS spectral indices. The results confirm that the modified C∗ ws can be used as a proxy of water stress that does not require concurrent information on meteorological data
Keywords: light use efficiency; Satellite data; Semi-natural vegetation; water stress

Application of BIOME-BGC to simulate Mediterranean forest processes - Chiesi, M; Maselli, F; Moriondo, M; Fibbi, L; Bindi, M; Running, S W (Ecological Modelling, 2007)
The current work investigates on the applicability of a widespread bio-geochemical model (BIOME-BGC) to estimate seasonal photosynthesis and transpiration within water limited Mediterranean forest environments. The use of the model required a preliminary calibration phase, aimed at setting its ecophysiological parameters to properly simulate the behavior of three Mediterranean species (Quercus ilex L., Quercus cerris L. and Pinus pinaster Ait.). For each of these species, the calibration of BIOME-BGC was performed by adjusting the monthly gross primary productivity (GPP) estimates of 10 forest plots to those of a simpliﬁed parametric model, C-Fix, which is based on the use of satellite and ancillary data. In particular, BIOME-BGC was run modifying the eco-physiological parameters controlling stomatal conductance, in order to identify the best model conﬁgurations to reproduce the spatial, intraand inter-annual GPP variations simulated by C-Fix. Next, the fraction of leaf nitrogen in Rubisco was adjusted to ﬁt also the magnitudes of the C-Fix GPP estimates. The subsequent testing phase consisted of applying the original and calibrated versions of BIOME-BGC in independent forest sites where the three species considered were dominant and for which ﬁeld measurements of photosynthesis and transpiration were available. In all cases the use of the calibrated BIOME-BGC versions led to notably improve the GPP and transpiration estimation accuracy of the original model. The results obtained encourage the operational application of BIOME-BGC in Mediterranean forest environments and indicate a possible strategy to integrate its functions with those of C-Fix.
Keywords: BIOME-BGC; C-Fix; GPP; mediterranean forest; monitoring; Spot-VGT